2002
DOI: 10.1038/sj.npp.1300097
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-Like Effect of Different Estrogenic Compounds in the Forced Swimming Test

Abstract: The present study evaluated the possible antidepressant-like action of the natural estrogen 17b-estradiol (E 2 , 2.5-10 mg/rat), the synthetic steroidal estrogen ethinyl-estradiol (EE 2 , 1.25-10.0 mg/rat), and the nonsteroidal synthetic estrogen, diethyl-stilbestrol (DES, 0.25-1.0 mg/ rat) in ovariectomized adult female Wistar rats using the forced swimming test (FST). The behavioral profile induced by the estrogens was compared with that induced by the antidepressants fluoxetine (FLX, 2.5-10 mg/kg) and desip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
3
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 83 publications
6
126
3
5
Order By: Relevance
“…A similar pattern is observed in animal models. In naturally receptive rats, or OVX rats administered E 2 regimen that produce physiological E 2 levels, anxiety and depression behaviors are decreased (Estrada-Camarena et al, 2003;Frye et al, 2000;Walf, 2002, 2004;Frye and Wawrzycki, 2003;Nomikos and Spyraki, 1988;Rachman et al, 1998;Slater and Blizard, 1976;Frye, 2005a, b, 2006). Thus, these data suggest that E 2 can alter affective responses.…”
Section: Introductionmentioning
confidence: 99%
“…A similar pattern is observed in animal models. In naturally receptive rats, or OVX rats administered E 2 regimen that produce physiological E 2 levels, anxiety and depression behaviors are decreased (Estrada-Camarena et al, 2003;Frye et al, 2000;Walf, 2002, 2004;Frye and Wawrzycki, 2003;Nomikos and Spyraki, 1988;Rachman et al, 1998;Slater and Blizard, 1976;Frye, 2005a, b, 2006). Thus, these data suggest that E 2 can alter affective responses.…”
Section: Introductionmentioning
confidence: 99%
“…Using this model (FST), the estrogens 17b-estradiol (E 2 ) and ethynil-estradiol (EE 2 ) have been found to produce antidepressant-like actions (Estrada-Camarena et al, 2003). An important difference between these two estrogens is that the natural estrogen E 2 is more potent at the serotonergic than at the noradrenergic system in decreasing re-uptake sites (Ghraf et al, 1983;Michel et al, 1987), while the synthetic steroidal compound EE 2 inhibits with a comparable efficacy the serotonergic and catecholaminergic sites (Ghraf et al, 1983;Michel et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the administration of estradiol benzoate for 7 or 14 days, induces antidepressant-like effects in the FST (Okada et al, 1997;Rachman et al, 1998). Besides, the antidepressant-like action of estrogenic compounds like 17 -estradiol (E2), 17 -ethinyl-estradiol (EE2) and diarylpropionitrile (DPN, an agonist to estrogen receptors type ) was also observed after an acute treatment (Estrada-Camarena et al, 2003;Walf et al, 2004). Interestingly, a selective estrogen receptor modulator, raloxifene, was only effective after 7 days of treatment; whereas tamoxifen, or the ER agonist, 4,4',4''-(4-Propyl-[1H]-pyrazole-1,3,5-triyl)trisphenol (PPT) were ineffective in the FST after an acute or chronic treatment (table 3).…”
Section: Antidepressant-like Effects Of Estrogens On Basic Researchmentioning
confidence: 99%
“…Studies in monkeys showed that E2 and the selective modulators of estrogen receptors, raloxifene and arzoxifene, increased tryptophan hydroxylase mRNA expression and decreased SERT's mRNA expression Smith et al, 2004). Interestingly, in the FST, raloxifene induced antidepressant-like effects similar to SSRIs such as fluoxetine (Estrada-Camarena et al, 2003;Estrada-Camarena et al, 2010). Studies in rats, analyzing different brain areas, indicate that acute or chronic treatment with estradiol benzoate decreased the number of 3 [H] paroxetine binding sites (Mendelson et al, 1993).…”
Section: Evidence Of Estrogens Interactions With the Serotonegic Systemmentioning
confidence: 99%